A self‐report measure of legal and administrative aggression within intimate relationships. Issue 4 (31st May 2014) - Hines, Denise A.; Douglas, Emily M.; Berger, Joshua L.
Abstract : Although experts agree that intimate partner violence (IPV) is a multidimensional phenomenon comprised of both physical and non‐physical acts, there is no measure of legal and administrative (LA) forms of IPV. LA aggression is when one partner manipulates the legal and other administrative systems to the detriment of his/her partner. Our measure was developed using the qualitative literature on male IPV victims' experiences. We tested the reliability and validity of our LA aggression measure on two samples of men: 611 men who sustained IPV and sought help, and 1, 601 men in a population‐based sample. Construct validity of the victimization scale was supported through factor analyses, correlations with other forms of IPV victimization, and comparisons of the rates of LA aggression between the two samples; reliability was established through Cronbach's alpha. Evidence for the validity and reliability of the perpetration scale was mixed and therefore needs further analyses and revisions before we can recommend its use in empirical work. There is initial support for the victimization scale as a valid and reliable measure of LA aggression victimization among men, but work is needed using women's victimization's experiences to establish reliability and validity of this measure for women. An LA aggression measure should be developed using LGBTQ victims' experiences, and for couples who are well into the divorce and child custody legal process. Legal personnel and practitioners should be educated on this form of IPV so that they can appropriately work with clients who have been victimized or perpetrate LA aggression. Aggr. Behav. 41:295–309, 2015. © 2014 Wiley Periodicals, Inc.